The Effect of Ism Code Implementation and Crew Competence on Safety Awareness which Impact on Prevention of Work Accidents by Ship Crew at PT Asia Maritim Temas - Sriyanti, Iis Elsya; Cahyadi, Tri; Yando, Markus; Herawati, Susi (Dinasti Publisher, 2025)
This study aims to analyze the impact of ISM Code Implementation and Crew Competence on Safety Awareness and its effect on Work Accident Prevention among crew members at PT Asia Maritim Temas. The main issue faced is the low level of safety awareness and the high number of work-related accidents among crew members, which affects the operational safety of the vessels. This research employs a quantitative approach with a cross-sectional design, involving 155 ship officers selected through saturated sampling. Data collection was done using questionnaires, and the data were analyzed using SmartPLS to examine the direct and indirect effects between the variables. The results show that ISM Code Implementation has a significant effect on Safety Awareness and Work Accident Prevention (t-value = 3.750), while Crew Competence also has a significant effect on Safety Awareness and Work Accident Prevention. Both variables also have an indirect effect on Work Accident Prevention through Safety Awareness. The conclusion of this study is that the implementation of the ISM Code and the enhancement of crew competence can improve safety awareness, which in turn can prevent work accidents on board. It is recommended to strengthen the implementation of ISM Code and safety training programs for crew members. Future research could explore this topic in more depth using a qualitative approach to better understand the challenges and perceptions of crew members regarding the implementation of safety measures